Penerapan Metode Teorema Bayes Dalam Mendiagnosa Penyakit Autoimun - Karim, Abdul; Esabella, Shinta; Kusmanto, Kusmanto; Suryadi, Sudi; Purba, Elvitrianim (Building of Informatics, Technology and Science (BITS), 2023)
Autoimmune diseases are caused by the failure of the immune system to attack the body itself. According to data from the US Department of Health and Human Services, more than 23.5 million Americans have an autoimmune disease, which is difficult to diagnose because of the variety of symptoms it presents. Therefore, the development of mechanisms to identify autoimmune disorders is essential. One of the developing technologies in this field is the use of expert systems in diagnosing diseases. An expert system is a system developed by experts using science-based technology. In order to use it effectively, proper methods are needed, such as the Bayes Theorem approach, described by Thomas Bayes, a priest. The Bayes Theorem approach explains the relationship between the probability of event A and event B based on available information. This study attempts to facilitate the diagnosis of autoimmune diseases by using an expert system and Bayes' Theorem technique. With a confidence level of 0.57 or 57%, the examination results show that the patient suffers from an autoimmune disease of the type Hemolytic Anemia (HA) based on the patient's input